Capacitación Laboral: Área de Oportunidad Eficaz en Alumnos de la Facultad De Ingeniería Mecánica y Eléctrica de la Universidad Autónoma de Nuevo León, Caso de Estudio. - Herrera, Emmanuel F.; Burgoa, Tabata (Revista Daena: International Journal of Good Conscience, 2026)
Job training ensures fulfill functions and activities efficiently, responds to the needs presented Organizations that counts with qualified, effective and productive human resource to enhance productivity and professional - personal performance. Of the 300 students who are studying in this Faculty as part of their job training, 217 the 72.33 % reported that they are working ; 38 of them mentioned that they receive support (grant ) by their chiefs or directors of companies where they work, and this represents, the 17.51 %, while 145 of the 217 mentioned that they do not receive any support and this represents the 62.88 % ; therefore we can see that students that are studying this technical degree as part of their training and work do not have support from the companies that they are now working . However, when asked if they had applied for scholarship support or their bosses or directors of the company where they work 183 answered this question: 48 yes and 135 mentioned that not and this represented 26.23 and 73.77 % ; 165 respondents total received a response to their request, 32 of them answered yes and 133 did not received support, so the 48 who applied 32 of them where supported by their companies, and this represents 66.66 %, then this may reflect that companies alone do not provide support training to their workers, perhaps most important reasons that exist within and outside the company.